Compressive Strength Analysis of Composite Blocks Made from Glass Powder and Plastic Waste - Isra, Muhammad; Syntia, Rita; Harmin, Amalia; Putra Wiratama, Andika; Febi Kurnia Sari, Ceni (Fakultas Teknik Universitas Samudra, 2024)
Efforts to manage waste are being undertaken at all levels, from households to large factories that produce waste daily. The imbalance between waste production and management has made waste a significant environmental issue. One of the most challenging types of waste to decompose naturally (non-biodegradable) is plastic waste, which constitutes the largest quantity compared to other types of waste. According to statistical data, the amount of non-biodegradable waste disposed of daily at final disposal sites in several cities in Indonesia is 6,598.23 tons per day. This research has both general and specific objectives. The general objective is to utilize plastic waste as a material for making paving blocks, while the specific objective is to analyze the compressive strength properties of paving blocks made from plastic waste. By exploring the potential of plastic waste in construction materials, this study aims to provide a sustainable solution to the plastic waste problem and contribute to environmental preservation. This study used 4 types of specimens where Specimen A consisted of 80% plastic waste and 20% glass powder. Specimen B consisted of 60% plastic waste and 40% glass powder, Specimen C consisted of 40% plastic waste and 60% glass powder, Specimen D consists of 20% plastic waste and 80% glass powder. The research results showed that Specimen B achieved the highest average compressive strength value of 10.9 Mpa, indicating significant potential in supporting material strength. On the other hand, Specimen D showed the lowest average compressive strength value with only 1.2 Mpa, indicating the need for further composition adjustments to increase the material's strength. This research provides valuable insight into developing recycled materials for construction and other industrial applications.